The types of Anthomyiidae (Diptera) in the Shanghai Entomological Museum, Chinese Academy of Science, China - Zhang, Xufeng; Zhu, Weibing (Zootaxa, 2014)
An annotated list of the type-specimens of Anthomyiidae deposited in the Shanghai Entomological Museum, China, is presented. A total of 196 holotypes and 479 paratypes representing 212 nominal species (207 valid, 5 synonyms) were recognized and are listed alphabetically. Bibliographical data of the original description, labels and condition of the type-specimens and the current name of the species are provided. At the end, a nomenclatural summary and a geographic summary are provided.